INOVASI IDENTITAS KEPENDUDUKAN DIGITAL DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PALU - Diwanti, Julia Oxana; Riadi, Slamet; Salingkat, Syarif Permana (JPS: Journal of Publicness Studies, 2025)
This research aims to find out the Innovation of Digital Population Identity at the Population and Civil Registration Office of Palu City. The research method used is Descriptive Qualitative, which provides a description of the phenomenon or focus of the problem being studied that occurs at the research location according to existing facts. The data collection techniques used are observation, in-depth informant interviews and documentation. The theory used in this study is the theory of Everett M. Rogers using five indicators, namely Relative Advantage, Compatibility, Complexity, Triability, Observability. Digital Population Identity Innovation has not gone well, where Digital Population Identity Innovation does not have advantages and more value so that it is considered still not good and has not provided a real solution to population administration services, has not succeeded in achieving the value of community needs and the demands of technological development and there are still people who experience difficulties, namely disruptions in the system that hinder the process and the ability of the community to understand a technology, the trial phase of the Digital Population Identity (IKD) application directly to the community in Palu City and the socialization carried out is not optimal. All forms of this problem need improvement so that in the future it can run well.